Survey instrument development and validation to measure technology adoption in dental hygiene clinical environments. Issue 7 (30th April 2020) - Delacruz, Natalie M.; Carlson, Brandi N.; Smith, Barbara S.
Abstract: Purpose: This pilot study aimed to develop and test a comprehensive assessment instrument, through an examination of measurement properties, to evaluate relationships between faculty technology adoption and age, level of education, teaching experience, technology anxiety, perceived technology integration barriers, and technology available in dental hygiene (DH) clinical environments. Focus was to acquire instrument validity with emphasis on test content, internal structure, and response processes. Methods: The survey was developed based on expert review, pretesting, and survey piloting in 2018. Three content experts evaluated face and traditional content validity. Eleven DH faculty with diverse clinical experiences were recruited for pretesting to comment on item definitions and language. The instrument was pilot tested among DH faculty with full‐time, part‐time, and clinical appointments at institutions located in the Mid‐West. Psychometric properties of the questionnaire were evaluated with frequency analysis and scale responses detailed. Results: Evaluation by experts and faculty members refined definitions, language, and response options for the seventy‐item response scale. Forty‐three DH faculty completed the online pilot. The 4 sections subjected to factor analysis showed excellent factor loading. Internal consistency was satisfactory. Frequency analysis showed an array of perceived abilities and technological integration in the educational environment. Conclusion: Findings suggest that respondents found the survey easy to complete and understand. The survey appears to be a valid measure of technology adoption among DH faculty of differing experiences. The survey will now be disseminated to a larger group of DH faculty.